Política Nacional de Resíduos Sólidos do Brasil e sua aplicabilidade na gestão integrada em aterro sanitário : estudo de caso no município de Gravatá/PE - Magalhães, Maria Lucivânia Cavalcanti da Silva (My University, 2025)
The context of the research concerns the challenges faced by municipal management in view of the increasing generation of solid waste, the environmental impacts resulting from inadequate disposal, and the need for sustainable solutions. The research has the general objective of analyzing the applicability of the National Solid Waste Policy (Law No. 12,305/2010) and the New Regulatory Framework for Basic Sanitation (Law No. 14,026/2020) in the integrated management of solid waste in sanitary landfills, through a case study in the municipality of Gravatá, in Pernambuco. The methodology adopted is qualitative, with a hypothetical-deductive approach and a cross-sectional nature, using a bibliographic review, legislative analysis, and diagnosis of socioenvironmental data from the municipality. The results demonstrate that, although there are legal and institutional advances in Brazil, the implementation of the guidelines provided for in environmental legislation encounters significant obstacles in the local reality, such as failures in inspection, low awareness of the population, and precarious public infrastructure. Most small Brazilian municipalities face difficulties in complying with legislation, either due to the lack of wareness among authorities about waste management or due to the lack of financial resources to acquire the equipment necessary for the collection, transportation and proper disposal of waste. The case study shows that the Gravatá landfill operates wth technical, social and environmental limitations that compromise its sustainability, despite its potential for generating biogas as a renewable energy source. The analysis also points to the need for integrated and participatory management, involving the government, the private sector and civil society, based on the shared responsibility provided for by law. It is concluded that the full implementation of Brazilian environmental legislation in solid waste management requires not only political will and technical resources, but also educational actions, territorial planning and technological innovation. Gravatá's experience shows that sustainable solutions are viable, as long as they are accompanied by effective environmental governance strategies. [resumo fornecido pelo autor]
O contexto da pesquisa tange aos desafios enfrentados pela gestão municipal diante da crescente geração de resíduos sólidos, dos impactos ambientais decorrentes do descarte inadequado e da necessidade de soluções sustentáveis. A pesquisa tem como objetivo geral analisar a aplicabilidade da Política Nacional de Resíduos Sólidos (Lei n. 12.305/2010) e do Novo Marco Regulatório do Saneamento Básico (Lei n. 14.026/2020) na gestão integrada de resíduos sólidos em aterros sanitários, por meio de um estudo de caso no município de Gravatá, em Pernambuco. A metodologia adotada é qualitativa, com abordagem hipotético-dedutiva e caráter transversal, utilizando-se de revisão bibliográfica, análise legislativa e diagnóstico de dados socioambientais do município. Os resultados demonstram que, embora existam avanços legais e institucionais no Brasil, a efetivação das diretrizes previstas na legislação ambiental encontra entraves significativos na realidade local, como falhas na fiscalização, baixa conscientização da população e precariedade na infraestrutura pública. A maioria dos municípios brasileiros de pequeno porte enfrenta dificuldades para se adequar à legislação, seja pela falta de conscientização das autoridades sobre a gestão de resíduos, seja pela escassez de recursos financeiros para adquirir equipamentos necessários à coleta, transporte e destinação adequada do lixo. O estudo de caso evidencia que o aterro sanitário de Gravatá opera com limitações técnicas, sociais e ambientais que comprometem sua sustentabilidade, apesar do potencial de geração de biogás como fonte energética renovável. A análise ainda aponta a necessidade de uma gestão integrada e participativa, que envolva o poder público, o setor privado e a sociedade civil, com base na responsabilidade compartilhada prevista em lei. Conclui-se que a implementação plena da legislação ambiental brasileira na gestão de resíduos sólidos exige não apenas vontade política e recursos técnicos, mas também ações educativas, planejamento territorial e inovação tecnológica. A experiência de Gravatá revela que soluções sustentáveis são viáveis, desde que acompanhadas por estratégias de governança ambiental eficazes. [resumo fornecido pelo autor]
Keywords: Aterro sanitário - Gravatá (PE); Resíduos sólidos; Biogás; Sustentabilidade; Direito ambiental; Sanitary landfills - Gravatá (Brazil); Solid waste; Biogas; Sustainability; Environmental law